Antimicrobial efficacy of liquorice extracts on most common endodontics pathogens - Kalaiselvan Abinaya; Rajsekaran Divya; Jeyakumar Asha; Anirudhan Subha; Suresh Kumar Sneha; Pazhamalai Adhityavasun (Wolters Kluwer Medknow Publications, 2023)
Aim: The purpose of this study is to evaluate the Antimicrobial effect of liquorice extracts and compare its action to commonly used root canal medicaments like calcium hydroxide and chlorhexidine against Enterococcus faecalis and Candida albicans. Materials and Methods: Ethanolic and aqueous extracts of liquorice root were prepared. Antimicrobial activity was tested by agar well diffusion method on E. faecalis and C. albicans using Mueller Hinton agar. Wells were prepared and filled with ethanolic extract, aqueous extract of liquorice, calcium hydroxide, and chlorhexidine. Samples were incubated at 37°C, zone of inhibition was examined after 24 h. Results and Statistical Analysis: Ethanolic extract was significantly better (P < 0.001) than calcium hydroxide and aqueous extract of liquorice and less effective than chlorhexidine against E.faecalis. In C. albicans, ethanolic extract was less significant (P < 0.001) when compared to calcium hydroxide and chlorhexidine. Conclusion and Clinical Relevance: Ethanolic extract of liquorice has potent bactericidal effect against E. faecalis and C. albicans over aqueous extract. Hence, it can be used as intracanal medicaments in routine endodontic therapy.